Ionic composition of Late Pleistocene composite sand-ice wedges of the Upper Sand unit of the Batagay megaslump - Yurij K Vasil extquotesinglechuk (PANGAEA, 2025)
Ionic composition of Late Pleistocene composite sand-ice wedges of the Upper Sand unit of the Batagay outcrop. Ice samples were collected from composite sand-ice wedges vertically every 10-20 cm using Makita DDF481rte18B and Bosch GSR 36 VE-2-LI drills with steel ice crowns with a diameter of 51 mm. To clean the sampling site, a 2-3 cm thick near-surface layer was removed from the surface of the composite sand-ice wedges using a drill, and then deeper samples were collected from the same hole. A sample consisting of sand and ice with a diameter of 5 cm was drilled from the sand-ice wedges, with the mass of each sample being about 150 g, and packed in polyethylene bags. The coordinates of the sand-ice veins were recorded using GPS. For samples from composite sand-ice wedges, a method was used to measure the mass concentration of Ca2+, Mg2+, Na+, K+, NH4+ cations in samples of drinking, mineral, natural and waste water by ion chromatography FR.1.31.2005.01738. For the determination of anions, the method of measuring the mass concentration of Cl-, SO4-, NO3- in samples of drinking, mineral, natural and wastewater by ion chromatography FR.1.31.2005.01724 was used. The method of measuring the mass concentration of ions in samples of natural, drinking and wastewater by ion chromatography HDPE F 14.1:2:4. 132-98. Measuring instruments: ion chromatographic system "Stayer", detection limit for chloride ion 0.02 mg/L. The acidity and electrical conductivity of melt water were measured using pH and EC meters.